Malocclusion detection in an effort to improve dental and oral health and prevent stunting during the COVID-19 pandemic - Rahmawati, Dwi; Ardani, I Gusti Wahju Aju; Nugraha, Alexander Patera (Indonesian Journal of Dental Medicine, 2025)
Background: Dental caries remains one of the primary health problems. Stunting has become a critical health priority in Indonesia, representing a nutritional disorder that results in children having lower height compared to their peers. There was a significant relationship between oral health problems and growth stunting, where dental and oral health issues can contribute to stunting development, and vice versa. Early detection of malocclusion is crucial for preventing complications and can provide both short-term and long-term benefits in maintaining optimal growth and development. Purpose:  to enhance dental and oral health knowledge for malocclusion detection as an effort to prevent stunting among elementary school children during the corona virus disease-19 (COVID-19) pandemic. Methods: This analytical observational study was conducted at SDN Medowo III, Kediri Regency, East Java, involving 100 participants from grades 4, 5, and 6. Intervention by video education and presentation education booklet. Data collection was performed through pre-test and post-test questionnaires. Frequency distribution analysis was conducted using SPSS version 23. Results: The study showed significant improvement in dental and oral health knowledge across all grade levels. Pre-test scores for dental health knowledge were 58%, 64%, and 60% for grades 4, 5, and 6, respectively, which increased to 80%, 82%, and 85% in post-test evaluations. Similarly, stunting knowledge improved from 59%, 68%, and 70% in the pre-test to 80%, 81%, and 83% in the post-test across the respective grades. Conclusion: The educational intervention effectively enhanced elementary school children's knowledge regarding dental and oral health and stunting prevention during COVID-19.